Sinkronisasi Antara Ketetapan Menteri Hukum Dan Hak Asasi Manusia Mengenai Penetapan Honor Kurator Dan Pengurus Dengan Ketentuan Undang-Undang Nomor 37 Tahun 2004 Tentang Kepailitan Dan Penundaan Kewajiban Pembayaran Utang - Yohanes Sebastian Tambunan (Iuris Studia: Jurnal Kajian Hukum, 2022)
The bankruptcy mechanism is needed as a legal framework in the economy. A company that facing financial difficulties may eventually become unable to continue operations, and be threatened with closure or liquidation. Corporate debt can also be obtained from non-bank financial institutions, such as leasing. When the company is declared bankrupt by the court, all this debt must be paid pro rata. The curator is appointed by the Court to make settlement of the bankruptcy estate which is supervised by the Supervisory Judge. The curator can immediately make settlement of the bankruptcy estate after the Court finds the Company in bankruptcy. For the services of the curator in carrying out the settlement task, the Bankruptcy Law regulates the provision of remuneration to the curator. Article 76 of Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations states that the Fee for Curator and Management Services is determined based on guidelines established by a decision of the Minister whose duties and responsibilities are in the field of law and legislation. The regulatory guidelines regarding Curator Fees have been changed six times since 1998. Changes for improvement were made due to the dynamics that emerged or pros and cons after the court determined the Curator's honorarium